The Impact of Family Dynamics on Marketing Performance: The Role of Marketing Agility as a Mediating Variable in the Context of SMEs. - Wisanggeni bagus Anggoro; Weni Novandari; Refius Pradipta Setyanto (International Journal of Business and Quality Research, 2024)
Tis Article discuss the impact of family dynamics on the marketing performance, with marketing agility as a mediating variable. This research is quantitative research that conducted in SME sector. The data was collected thrugh 5 resiident in central java, using sample of 150 SME using 5 point likert scale. The data was analyzed througe structured equation modeling. Result found that Family dinamics has indirect impact on marketing performance this becaise the family dynamics will impacting the ability of a company to do the marketing agility. This research recommend the family corporate should do the best way to get the marketing agility so they can increase their market performance. This research limit on its rage for only has been done in 5 resident in central java, so the next research should enlarge the sample of the study.